PERAN AGEN HAYATI ASAL RIZOSFER DAN ENDOFIT MENEKAN PENYAKIT BUSUK SKLEROTIUM ROLFSII BAWANG DAUN DI MEDIA GAMBUT (Role of Rhizosphere and Endophytes Biological Agents to Supress Sclerotium rolfsii Rot Disease on Scallions in the Peat Media): Mulyani, R. B.,1*), Usup, A.,1), Supriati, L1), dan Ramlan1) - Admin journal (AgriPeat, 2018)
ABSTRACTThe Sclerotium Rot Disease is highly destructive to the scallions cultivation in the peat soil. Theantagonistic fungi isolated from the rhizosphere and the endophytes of healthy plants, have beenproven to be able to reduce Sclerotium rolfsii. The aim of this study was to evaluate thecharacteristics of antagonistic fungi from rhizosphere and endophytes of Scallions to S. rolfsii in- vitro in the laboratory. The purpose of this study was also to perform the suppression test on theintensity of Sclerotium rolfsiiRot Disease in planta in the peat media in the screen house. Thisresearch it was shown that genus Fusarium, Penicillium, Aspergillusas antagonistic fungi, wereidentified from the endophytes, meanwhile genus Trichoderma, Penicillium dan Aspergillus sp. were identified from the rhizosphere. Trichoderma Rz-1 and Trichoderma Rz-3 isolated from therhizosphere was shown to have the highest antagonistic activity by 94,4 %, followed by AspergillusEd-2, which was isolated from the endophytes by 83,8%. In planta on peat media, TrichodermaRz-1 was capable to demonstrate 82,19% of antagonistic effect and it could suppress SclerotiumRot Diseasehence it produced the fresh weight of the plant highest to 19gcluster-1. Taken together,the result of this study showed that Trichoderma Rz-1 isolated from rhizosphere has been proven tobe the most beneficial to reduce the Sclerotium rolfsii on Scallions as a biological control agent,especially in peat soils.Keywords: biocontrol, rhizosphere,endophyte, scallions, Sclerotium rolfsii